Perioperative hemodynamic status in children with acquired hydrocephalia. - Snisar, V. I.; Skliar, V. V.; Lisivets, V. I. (Medicni Perspektivi, 2014)
This article demonstrates the main features of hemodynamic parameters in children with acquired hydrocephalia, as well as the dynamics of changes in these parameters on the background of total intravenous anesthesia using sodium thiopental and inhalation anesthesia with sevoflurane on the background of ventricular-peritoneal shunting. 75 children aged 6,72±3,21 months with acquired form of hydrocephalia who underwent ventricular-peritoneal shunting were included in the study. Comparing with control group, children with acquired hydrocephalia had sighnificantly higher SV and CO (hyperkinetic variant) and decreased SVR. Based on the model of "Windkessel", this change of relationships of hemodynamic parameters may be explained as follows: under moderate intracranial hypertension, when autoregulation of cerebral blood flow is extremely tense and centralization of circulation is not effective enough, the increase in cardiac output provides support of systolic components of CPP. A multifactorial analysis has shown that HR incidence increased after premedication in TIVA group by 8.6% versus 5.8% in IA group from initial value. There was no sighnificant differences between groups (р>0.05). Maximum HR performance decreased at the fourth stage: 21.6% from the initial value in TIVA group (p<0.05), and 19.02% - in IA group (p<0.05), however, significant differences between groups at this stage and at the end of the operation were not noted (p>0.05). In our study, a significantly greater (p<0,05) SBP, DBP and MAP findings in TIA group drop, especially at the fourth stage (MAP by 18.49% from baseline). This it is really connected with the decrease of SVR (by 30.3% from baseline). In IA group on the background of BP reduction the growth of APS by 7.2% from baseline and MAP by 4.3% from baseline at the fourth stage was detected. CO in TIVA group reduced and in IA group it increased. Moreover, in IA group more significant increase of SV was marked. This testifies to the fact that during sevoflurane anesthesia the mobilization of CO takes place, activating mechanisms of heart functions. The results demonstrate that level of experienced stress at the end of the surgery did not exceed normal findings in both groups.